Pengaruh Sumber Daya Manusia Dalam Pengembangan Digital Marketing Terhadap Minat Beli : (Studi Kasus : Toko Sumber Usaha Sumba Barat Daya) - Robertus Tamo Ama; Delsiana Kette; Ancelina Bili; Meriana Milla (Asosiasi Riset Ilmu Teknik Indonesia, 2024)
This research aims to investigate the influence of human resources in digital marketing development on consumer purchasing interest, at business source stores. The research method used is quantitative using a questionnaire as a data collection tool. The sample for this research is consumers of business source stores who have made online transactions. Data analysis was carried out using multiple linear regression to test the relationship between digital marketing human resource variables and consumer buying interest. The research results show that human resources who are skilled and experienced in digital marketing have a positive and significant influence on consumer buying interest. The managerial implication of this research is the importance of investing in developing quality human resources in the digital marketing field to increase consumer buying interest and strengthen the competitive advantage of business resource stores in the market.